ANALISIS PUISI “JARAK” KARYA HERI ISNAINI DENGAN PENDEKATAN SEMIOTIKA - siti nurjanah (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The aim of this study is to describe a poem of "Jarak" by Heri Isnaini by using a semiotics approach. The article is focused on the marking aspect that appears throughout the poem which is analyzed to represent the sense of the meaning. This research is motivated by the author's interest in the contents of the poem which provides an overview of how closely related humans are to death. Only death can separate the two lives with a very secret time. The method uses qualitative descriptive method. The data analysis technique was carried out by: (1) reading poetry, (2) understanding the meaning of every verse in the poetry, (3) analyzing poetry with a semiotics approach, (5) concluding the results of the analysis. The results show that the dominant sign in the poem "Jarak" is index. An index is a sign that gives an idea of the causal relationship between the object. The object used in this poem has a difference in each stanza. Although the object used is different, but has the same meaning, which explains how the relationship humans and death. Death becomes a transfer from the realm of the world to the barzakh realm, which is the realm of separation between the world and the hereafter. Therefore, this poem is highly recommended for all people, old as well as young, to always prepare provisions for worship and good deeds for prepare for life after death.